The Role of Institutes for Advanced Study in Promoting Internationalization - Rüland , Dorothea; Gräber-Magocsi, Sonja (International Higher Education, 2022)
Since 1930, more than 150 Institutes for Advanced Study have been founded all over the world. They have a common role in the global science system in that they all aim to promote innovation and free spaces for researchers. The future of internationalization in research and higher education might lie in a strong focus on the development of global networks.